Studies on the amides of Coconut oil fatty acids - Rodriguez, Asuncion R.
Coconut oil fatty acid amides were prepared by reacting coconut oil fatty acids obtained by hydrolysis with sulfuric acid, with phosphorus trichloride and treating with concentrated ammonia, the fatty acid amides being isolated by recrystallization from carbon tetrachloride. The softening point of the mixed fatty acid amides was 61.6oC. This mixture was blended with a sugar-cane wax fraction and also with ester gum obtained from glycerol and Manila copal. The blends have softening points of 71.5 and 91.8o, respectively. The fatty acid amides as well as the blended products are all waxy in appearance and can be used as lustering agents when suitably dispersed in a solvent.